Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Kontekstual Pada Mata Pelajaran Sejarah Kelas X di Sekolah Menengah Atas - LR. Retno Susanti; Alian Alian; Zulfachry Juhar (Criksetra: Jurnal Pendidikan Sejarah, 2017)
It is a research which entitled as “Development of Student’s Worksheet Based on Contextual Learning at Xth Grade in History Subject for Senior High School.” Its aim is to explain how to make a valid learning material for History Subjects. A measurement of this learning material in a kind of Student’s Worksheet must be scored by three experts like Learning Design’s Expert, Learning Material Expert, and Linguistic Expert. These are every point of validation that were given to Learning Material was made by researcher : Learning Design categorized as valid in average of 3,88, Learning Material categorized as valid in average of 3,75, and in Lingusitic categorized as valid in average of 3,77. This Learning Material potentially effected to students based on field test in Senior High School 7 of Palembang, field test that’s ever been done divided into two sections where Pre-Test shows a score of average 56,9 as a low result and Post-Test shows a higher result of average 84,7 From 0% as agregate of all students reached minimum standard of score for 38 person or 100 %. The result concludes Development of Student’s Worksheet Based on Contextual Learning at Xth Grade in History Subject for Senior High School is effectively used as a valid learning product.